Artificial Intelligence Awareness and Utilization Among Junior High School Science Teachers: A Descriptive Study from the Philippines - Ara Jabeniar Ganotisi; Rendel Bagang Batchar; Nicole Amber Black Cayanan; Judy Blando Dumlao; Nomaisa Lomodag Usman (Universitas Syiah Kuala, 2025)
The limited adoption of artificial intelligence (AI) tools in education hinders efforts to improve teaching and learning outcomes worldwide. Recognizing this challenge, the study aimed to assess the awareness and utilization of AI tools among junior high school science teachers in Dinalupihan, Bataan. Employing a descriptive cross-sectional quantitative design, data were gathered from 44 science teachers across public and private secondary schools through validated survey instruments. The awareness scale measured both cognitive and performance-related understanding of AI tools, while a utilization survey assessed the extent of AI tool use in instructional practices. Results indicated a high level of cognitive awareness (M = 3.70) but only moderate performance-related awareness (M = 3.34). Despite this, overall utilization of AI tools was low, with ChatGPT and Grammarly emerging as the most commonly used platforms. Non-parametric analyses revealed significant differences in awareness based on teachers length of service and type of school, suggesting that professional experience and institutional context influence familiarity and use of AI in education. These findings emphasize the need for contextualized professional development and training programs to bridge the gap between AI awareness and practical application, thereby enhancing science teaching and learning experiences